2015
DOI: 10.1111/eea.12307
|View full text |Cite
|
Sign up to set email alerts
|

Electrical penetration graphs indicate that tricin is a key secondary metabolite of rice, inhibiting phloem feeding of brown planthopper, Nilaparvata lugens

Abstract: Tricin (5,7,4′‐trihydroxy‐3′,5′‐dimethoxyflavone) is a valuable secondary metabolite which is widely present in gramineous plants, including cultivated rice (Oryza sativa L.) (Poaceae). It can defend the rice plant against damage by the brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), one of the most important pests of rice. This study was conducted to elucidate the mechanisms of action of tricin on BPH feeding behavior. BPH feeding behavior in resistant (Rathu Heenati, RHT) and sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 39 publications
(131 reference statements)
1
42
0
Order By: Relevance
“…Electrical Penetration Graph studies accomplished by Zhang et al. () showed that BPH nymphs had higher stylet probing frequencies and a shorter phloem feeding time in resistant rice varieties. Tricin is a key secondary metabolite of rice that inhibits BPH nymphs from feeding on phloem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Electrical Penetration Graph studies accomplished by Zhang et al. () showed that BPH nymphs had higher stylet probing frequencies and a shorter phloem feeding time in resistant rice varieties. Tricin is a key secondary metabolite of rice that inhibits BPH nymphs from feeding on phloem.…”
Section: Discussionmentioning
confidence: 99%
“…Velusamy and Heinrichs (1986), Hattori (2001) and Seo et al (2010) reported that feeding behaviour was different on resistant and susceptible rice varieties. Electrical Penetration Graph studies accomplished by Zhang et al (2015) showed that BPH nymphs had higher stylet probing frequencies and a shorter phloem feeding time in resistant rice varieties. Tricin is a key secondary metabolite of rice that inhibits BPH nymphs from feeding on phloem.…”
Section: Relationship Between Tricin Concentration and The Bph Resistmentioning
confidence: 99%
See 3 more Smart Citations